2019
DOI: 10.1021/jacs.9b10771
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies into the Oxidative Addition of Co(I) Complexes: Combining Electroanalytical Techniques with Parameterization

Abstract: The oxidative addition of organic electrophiles into electrochemically generated Co­(I) complexes has been widely utilized as a strategy to produce carbon-centered radicals when cobalt is ligated by a polydentate ligand. Changing to a bidentate ligand provides the opportunity to access discrete Co­(III)–C bonded complexes for alternative reactivity, but knowledge of how ligand and/or substrate structures affect catalytic steps is pivotal to reaction design and catalyst optimization. In this vein, experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
89
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(104 citation statements)
references
References 113 publications
11
89
0
2
Order By: Relevance
“…Cyclic voltammetric studies identified the existence of a catalytic waveform, 7 in agreement with the catalytic reduction of benzyl bromides to benzyl radicals by the Co(I) complex, and detailed kinetic studies unveiled trends in substrate variation consistent with an outer-sphere electron-transfer mechanism. This mechanistic proposal, distinctive from our previously studied system, 6 was further supported by multivariable linear-regression (MLR) analysis, 8 enabling us to identify that the electron transfer occurs in a concerted fashion with dissociation of bromide from the substrate. In addition, with the combination of the electroanalytical techniques 7 and statistical modeling, 8 we establish a pattern recognition platform for rapidly distinguishing between the activation mechanisms of different metal complexes (Scheme 1.c) 9 , a tool which we anticipate will be broadly applied in the rational design of new organometallic reactions.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…Cyclic voltammetric studies identified the existence of a catalytic waveform, 7 in agreement with the catalytic reduction of benzyl bromides to benzyl radicals by the Co(I) complex, and detailed kinetic studies unveiled trends in substrate variation consistent with an outer-sphere electron-transfer mechanism. This mechanistic proposal, distinctive from our previously studied system, 6 was further supported by multivariable linear-regression (MLR) analysis, 8 enabling us to identify that the electron transfer occurs in a concerted fashion with dissociation of bromide from the substrate. In addition, with the combination of the electroanalytical techniques 7 and statistical modeling, 8 we establish a pattern recognition platform for rapidly distinguishing between the activation mechanisms of different metal complexes (Scheme 1.c) 9 , a tool which we anticipate will be broadly applied in the rational design of new organometallic reactions.…”
Section: Introductionmentioning
confidence: 65%
“…For a more detailed explanation of this method, we direct the reader to previous studies. 5,6 This analysis allowed us to measure the rate constant for each substrate in less than 30 minutes, thus enabling us to rapidly conduct kinetic studies with a wide array of substrates.…”
Section: Determination Of Activation Rate Constantsmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations show that only the C F –S bond was cleaved, consistent with a concerted OA C–S activation pathway. 64 …”
Section: Resultsmentioning
confidence: 99%
“… (A, B) Mechanistic study of oxidative addition to Co I complex. Graphs in panel A are reproduced from ref ( 51 ). Copyright 2019 American Chemical Society.…”
Section: Electrochemistrymentioning
confidence: 99%